2015
DOI: 10.1016/j.jveb.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing companion dog behavior in a social setting

Abstract: 1There is a growing and important need for large-scale characterisation of dog 2 behaviour, for example to conduct genetic analyses or to assess welfare. An extensive 3 number of standardised tests and questionnaires are used for this, but few focus on the 4 normal behaviour in situations which are frequently encountered in the everyday life 5 of companion dogs. The aim of this study was to develop and validate a fast, but 6 standardised method to characterise behavioural variation in pet dogs, based on a brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…We found that female golden retrievers sought significantly more human eye contact than males. This is in agreement with previous results showing that human-directed social behavior in dogs differs between sexes where females seek more physical contact from humans than males (Persson et al, 2015;Roth and Jensen, 2015). Also, oxytocin treatment has been shown to have different sex dependent effects on human directed gazing, increasing looking behavior in females (Kovacs et al, 2016a;Nagasawa et al, 2015;Oliva et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…We found that female golden retrievers sought significantly more human eye contact than males. This is in agreement with previous results showing that human-directed social behavior in dogs differs between sexes where females seek more physical contact from humans than males (Persson et al, 2015;Roth and Jensen, 2015). Also, oxytocin treatment has been shown to have different sex dependent effects on human directed gazing, increasing looking behavior in females (Kovacs et al, 2016a;Nagasawa et al, 2015;Oliva et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Other simple quantitative tests can and should be developed that elucidate other dimensions of how dogs interact within their social world. Roth and Jensen (2015) noted effects of age, size of dog household and living condition on social behaviors, documenting environmental aspects of plasticity in behaviors, suggesting that this test should be replicated across breeds, jobs, living conditions (e.g., shelters), countries, and cultures. One has to believe more such papers should be anticipated.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The first line of the abstract of the paper by Roth and Jensen (2015), "There is a growing and important need for large-scale characterization of dog behavior, for example, to conduct genetic analyses or to assess welfare. ", flags its affinity with papers that precede it in this issue.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, aged dogs behaved more passively, showed less interest in an unknown person during separation from owners, and had a significantly increased stress response. This indicates that older dogs may not be as adept at managing social situations, especially since age decreases the sociability of the dog [22]. Interestingly, aging dogs also transition from spending a lot of time directly interacting with humans to simply spending more time near humans [23].…”
Section: Evidence That Therapy Work May Be Stressfulmentioning
confidence: 99%